Pyrolysis of Ca/Fe-rich antibiotic fermentation residues into biochars for efficient phosphate removal/recovery from wastewater: turning hazardous waste to phosphorous fertilizer - Zhang, Mingdong (2023)
Ca/Fe-rich antibiotic fermentation residues (AFRs), a type of hazardous waste, can be regarded as recyclable biomass and metal resources. However, concurrent detoxification and reutilization of biomass and metals resources from AFRs have never been reported before. In this study, Ca/Fe-rich vancomycin fermentation residues were pyrolyzed into biochar to adsorb phosphate for the first time. The residual vancomycin and antibiotic resistance genes were completely decomposed during pyrolysis. The resultant Ca/Fe-rich biochar exhibited excellent performance at adsorbing phosphate without further modifications. The process had rapid kinetics and a maximum adsorption capacity of 102 mg P/g. Ca and Fe were the active sites, whereas different mechanisms were observed under acidic and alkaline conditions. Surprisingly, HCO3- enhanced phosphate adsorption with an increase of adsorption capacity from 43.9 to 71.0 mg/g when HCO3- concentration increased from 1 to 10 mM. Furthermore, actual wastewater could be effectively treated by the biochar. The phosphate-rich spent biochar significantly promoted seed germination (germination rate: 96.7 % vs. 80.0 % in control group, p < 0.01) and seedling growth (shoot length was increased by 57.9 %, p < 0.01) due to the slow release of bioavailable phosphate, and thus could be potentially used as a phosphorous fertilizer. Consequently, the hazardous waste was turned into phosphorous fertilizer, with the additional benefits of detoxifying AFRs, reutilizing biomass and metal resources from AFRs, controlling phosphate pollution, and recovering phosphate from wastewater.